Adaptive mechanisms of athletes' bodies under extreme conditions - Denisenko, Y.; Ahmetov, A.; Semenov, S.; Andrushchishin, I. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to provide theoretical and experimental justification for the basic principles of constructing a comprehensive system of special relaxation training aimed at improving the functional state of athletes' bodies, increasing the rate of skeletal muscle relaxation, and improving the effectiveness of the training process.